PELAKSANAAN PROGRAM PENERTIBAN TRUK BERTONASE BERAT DI KOTA PEKANBARU TAHUN 2017 - Hesty Milanda; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
In order to improve the safety and comfort in traffic on public roads or in Pekanbaru urban areas, the government is controlling especially on heavy tonnage trucks. The government that has responsibility in controlling in this traffic is the Transportation Agency of Pekanbaru City. The problem faced is where heavy tonnage trucks pass on roads that are not allowed or enter the Pekanbaru City area, besides that there are still many heavy tonnage trucks passing at hours that are prohibited by the Transportation Agency.This study aims to determine the implementation of the heavy tonnage truck control program in Pekanbaru City in 2017, as well as the factors that have not yet achieved the implementation of the heavy tonnage truck control program in Pekanbaru City in 2017. Data collection techniques were carried out by interviews, and documentation. While the data analysis technique is done by qualitative data analysis. The results of the study that the Implementation of the Heavy Duty Trucking Control Program in Pekanbaru City in 2017 has not been achieved optimally seen from the implementation of the curbing program carried out by the Pekanbaru City Transportation Department, namely the Transportation Infrastructure and Construction of Special Bertonase Trucks and Controlling and Safeguarding of Heavy-Duty Trucks has not affected the changes occurring in the field, namely the increasing number of violations occurring in heavy tonnage trucks on urban roads and crossing during rush hour. Factors that cause the implementation of the control program have not been optimally achieved due to the lack of optimal implementation of the activities of the program. This is because there are several constraints on the lack of quality and quantity of human resources, budgetary resources, lack of optimal procurement of facilities and infrastructure and cooperation carried out between the Department of Transportation and related parties.Keywords: Communication, Resources, Disposition, Bureaucratic Structure.